Association between Magnesium Disorders and Hypocalcemia following Thyroidectomy. (September 2016) - Nellis, Jason C.; Tufano, Ralph P.; Gourin, Christine G.
Objective: To identify factors associated with postoperative hypocalcemia after thyroid surgery and to understand the relationship among hypocalcemia, length of hospitalization, and costs of care. Study Design: Retrospective database analysis. Methods: Discharge data from the Nationwide Inpatient Sample for 620, 744 patients who underwent thyroid surgery from 2001 to 2010 were analyzed through cross-tabulations and multivariate regression modeling. Hypocalcemia, length of stay, and costs were examined as dependent variables. Secondary independent variables included magnesium and phosphate metabolism disorders, vitamin D deficiency, menopause, sex, extent of surgery, malignancy, and surgeon volume. Results: Hypocalcemia was reported in 6% of patients and was significantly more common for the following variables: women, age <65 years, patients from the Northeast, total thyroidectomy ± neck dissection patients, low-volume surgical care, malignancy, recurrent laryngeal nerve injury, and patients with disorders of magnesium or phosphate metabolism ( P < .001). Magnesium and phosphate disorders were present in <1% of patients. Magnesium disorders were significantly more likely for patients with hypocalcemia (7%; P < .001), and hypocalcemia was present in 52% of patients with magnesium disorders ( P < .001). On multiple logistic regression analysis, the odds of hypocalcemia were greatest for patients with magnesium disorders (odds ratio, 12.71; 95% confidence interval, 8.59-18.82). This relationship was not attenuated by high-volume surgical care. Hypocalcemia and magnesium disorders were both associated with increased length of stay and costs, with a greater effect for magnesium disorders than for hypocalcemia ( P < .001). Conclusions: Disorders of magnesium metabolism are an independent risk factor for postthyroidectomy hypocalcemia and are associated with significantly increased costs and length of stay.